2001
DOI: 10.1046/j.1440-0960.2001.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact stomatitis caused by acrylic monomer in a denture

Abstract: A 71-year-old edentulous man developed a severely painful red mouth at sites of contact with a new denture. Patch testing showed allergy to samples of the denture material and to 2-hydroxyethyl methacrylate. Patch testing to methyl methacrylate was negative. Prolonged boiling of the denture resulted in reversal of his symptoms and samples of this fully cured denture material produced negative patch tests. While allergy to acrylates is a rare cause of stomatitis, this possibility must be considered in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 44 publications
1
44
0
2
Order By: Relevance
“…These data further support the need for treatment of the acrylic resin, such as polymerization in water or under pressure, [25][26][27] as well as allowing additional polymerization cycles. 5,[25][26][27][28][29] During the preparation of the acrylic appliance, it is also important to keep the right proportion of powder and liquid. 16,25 All these procedures can reduce the frequency of hypersensitivity reactions and help guarantee the patient's well-being.…”
Section: Discussionmentioning
confidence: 99%
“…These data further support the need for treatment of the acrylic resin, such as polymerization in water or under pressure, [25][26][27] as well as allowing additional polymerization cycles. 5,[25][26][27][28][29] During the preparation of the acrylic appliance, it is also important to keep the right proportion of powder and liquid. 16,25 All these procedures can reduce the frequency of hypersensitivity reactions and help guarantee the patient's well-being.…”
Section: Discussionmentioning
confidence: 99%
“…There are also more obscure exposures unique to the elderly detailed in the literature including benzyl alcohol in hearing aid impression material, [45] acrylic monomer in a denture, [46] coronary stent materials, [47] and implant materials for total knee and total hip arthroplasty. [48,49] Finally, conditions such as urinary fecal incontinence and ostomies following gastrointestinal or urologic procedures disrupt the natural skin barrier, predisposing to both irritant and allergic dermatitides.…”
Section: Medical Co-morbidities In Older Adultsmentioning
confidence: 99%
“…However, some authors have reported allergic reactions to an unbound monomer of acrylic materials [22, 29, 30]. …”
Section: Discussionmentioning
confidence: 99%